Molecular and biochemical characterization of urease and survival of Yersinia enterocolitica biovar 1A in acidic pH in vitro - Bhagat, Neeru (BioMed Central, 2009)
BACKGROUND: Yersinia enterocolitica, an important food- and water-borne enteric pathogen is represented by six biovars viz. 1A, 1B, 2, 3, 4 and 5. Despite the lack of recognized virulence determinants, some biovar 1A strains have been reported to produce disease symptoms resembling that produced by known pathogenic biovars (1B, 2-5). It is therefore imperative to identify determinants that might contribute to the pathogenicity of Y. enterocolitica biovar 1A strains. Y. enterocolitica invariably produces urease and the role of this enzyme in the virulence of biovar 1B and biovar 4 strains has been reported recently. The objective of this work was to study genetic organization of the urease (ure) gene complex of Y. enterocolitica biovar 1A, biochemical characterization of the urease, and the survival of these strains under acidic conditions in vitro. RESULTS: The ure gene complex (ureABCEFGD) of Y. enterocolitica biovar 1A included three structural and four accessory genes, which were contiguous and was flanked by a urea transport (yut) gene on the 3' side. Differences were identified in ure gene complex of biovar 1A strain compared to biovar 1B and 4 strains. This included a smaller ureB gene and larger intergenic regions between the structural genes. The crude urease preparation exhibited optimal pH and temperature of 5.5 and 65°C respectively, and Michaelis-Menten kinetics with a K(m )of 1.7 ± 0.4 mM urea and V(max )of 7.29 ± 0.42 μmol of ammonia released/min/mg protein. The urease activity was dependent on growth temperature and growth phase of Y. enterocolitica biovar 1A, and the presence of nickel in the medium. The molecular mass of the enzyme was > 545 kDa and an isoelectric point of 5.2. The number of viable Y. enterocolitica biovar 1A decreased significantly when incubated at pH 2.5 for 2 h. However, no such decrease was observed at this pH in the presence of urea. CONCLUSIONS: The ure gene cluster of biovar 1A strains though similar to biovar 1B and 4 strains, exhibited important differences. The study also showed the ability of biovar 1A strains of Y. enterocolitica to survive at highly acidic pH in vitro in the presence of urea.